Phyllanthus Niruri Standardized Extract Alleviates the Progression of Non-Alcoholic Fatty Liver Disease and Decreases Atherosclerotic Risk in Sprague–Dawley Rats - Al Zarzour, Raghdaa Hamdan; Ahmad, Mariam; Asmawi, Mohd. Zaini; Kaur, Gurjeet; Ahmed Saeed, Mohammed Ali; Al-Mansoub, Majed Ahmed; Mohammed Saghir, Sultan Ayesh; Usman, Nasiba Salisu; Al-Dulaimi, Dhamraa W.; Mun, Fei Yam (MDPI, 2017)
Non-alcoholic fatty liver disease (NAFLD) is one of the major global health issues, strongly correlated with insulin resistance, obesity and oxidative stress. The current study aimed to evaluate anti-NAFLD effects of three different extracts of Phyllanthus niruri (P. niruri). NAFLD was induced in male Sprague–Dawley rats using a special high-fat diet (HFD). A 50% methanolic extract (50% ME) exhibited the highest inhibitory effect against NAFLD progression. It significantly reduced hepatomegaly (16%) and visceral fat weight (22%), decreased NAFLD score, prevented fibrosis, and reduced serum total cholesterol (TC) (48%), low-density lipoprotein (LDL) (65%), free fatty acids (FFAs) (25%), alanine aminotransferase (ALT) (45%), alkaline phosphatase (ALP) (38%), insulin concentration (67%), homeostatic model assessment of insulin resistance (HOMA-IR) (73%), serum atherogenic ratios TC/high-density lipoprotein (HDL) (29%), LDL/HDL (66%) and (TC–HDL)/HDL (64%), hepatic content of cholesterol (43%), triglyceride (29%) and malondialdehyde (MDA) (40%) compared to a non-treated HFD group. In vitro, 50% ME of P. niruri inhibited -glucosidase, pancreatic lipase enzymes and cholesterol micellization. It also had higher total phenolic and total flavonoid contents compared to other extracts. Ellagic acid and phyllanthin were identified as major compounds. These results suggest that P. niruri could be further developed as a novel natural hepatoprotective agent against NAFLD and atherosclerosis.